Genomic Analysis as the First Step toward Personalized Treatment in Renal Cell Carcinoma - Bielecka, Zofia Felicja; Czarnecka, Anna Małgorzata; Szczylik, Cezary (Frontiers in Oncology, 2014)
Renal cell carcinoma (RCC) drug resistance mechanisms still remain elusive. Although most patients initially respond to targeted therapy (i.e. to tyrosine kinase inhibitors), acquired resistance can still eventually develop. Most of the patients suffer from intrinsic (primary) resistance as well, suggesting that there is a substantial need to broaden our knowledge in the field of RCC on a genetic basis. As molecular abnormalities are of various origins, ranging from single nucleotide polymorphisms to large chromosomal defects, conducting the genome-wide genetic analysis with the use of high-throughput techniques seems inevitable. In principle, data obtained via such research should be continued and performed on a large scale for the purposes of drug development and identification of biological pathways underlying cancerogenesis. Genetic alterations are mostly unique for each histological RCC subtype. According to recently published data, RCC is a highly heterogeneous tumor. Herein, the authors discuss: 1) current state-of-the-art knowledge on potential RCC subtypes’ biomarkers; 2) significant obstacles encountered in translational research on RCC and 3) recent molecular findings that may have crucial impact on therapeutic approaches in the future.